Šikšnosparnių įvairovė ir gausumas Vilniaus miesto žiemavietėse - Baranauskas, Kazimieras; Mickevičius, Eduardas; Mickevičienė, Ingrida (2005)
Diversity and abundance of hibernating bats were investigated in the Paneriai tunnel, Pavilniai, Šilas, Šeškynė, Kairėnai and Verkiai bats hibernation sites (Vilnius, Lithuania) in 1997-2004. Six bat species were found to hibernate: Daubenton's bat (Myotis daubentonii), pond bat (Myotis dasycneme), brown long-eared bat (Plecotus auritus), barbastelle (Barbastella barbastellus), serotine bat (Eptesicus serotinus) and northern bat (Eptesicus nilssonii). It was established that about 300 bats roost in the Vilnius hibernaculas every year, Daubenton's bats consistuting 43%, barbastelles 39% and pond bats 8%. That is the largest known hibernating clusters of Daubenton's bats, pond bats and barbastelles in southeastern Lithuania. Under the EU Habitats Directive, barbastelles and pond bats are considered to be mammals of European importance. The Paneriai tunnel is protected as an engineering monument. It is recomended that the Paneriai tunnel and Šilas bat hibernation site should be granted the status of bat reserves.